Understanding Electrochemical Alcohol Hydrogenolysis Enabled by Carbonyl Reduction in Lignocellulosic Biomass-Derived Aromatic Oxygenates - Myohwa Ko; Xin Yuan; Kwanpyung Lee; J. R. Schmidt; Kyoung-Shin Choi (Journal of the American Chemical Society, 2026)
Abstract Molecules derived from lignocellulosic biomass are oxygenates with multiple oxygen-containing functional groups, such as hydroxyl and carbonyl groups. Therefore, the ability to selectively reduce a specific oxygenate group is essential for the reductive upgrading of such molecules. Previous studies on electrochemical biomass conversion have shown that alcohol hydrogenolysis, which involves cleavage of the σ(C–Oalcohol) bond, is extremely challenging for furfural and 5-hydroxymethylfurfural (HMF) derivatives, including furfuryl alcohol, 5-methylfurfuryl alcohol (MFA), and 2,5-bis(hydroxymethyl)furan (BHMF). In contrast, HMF itself undergoes alcohol hydrogenolysis relatively easily in acidic aqueous media. Considering that the only structural difference between HMF and BHMF or MFA is the presence of a carbonyl group, this observation raises the question of whether the carbonyl group in HMF facilitates alcohol hydrogenolysis. In this study, we designed systematic experiments to provide a coherent explanation of when and how a carbonyl group enables hydrogenolysis of a copresent alcohol group. Specifically, we show that alcohol hydrogenolysis in HMF proceeds via reduction of the carbonyl group to a ketyl radical, followed by a spin-center shift (SCS) through extended π conjugation. We also elucidate the effect of pH on the selectivity between carbonyl hydrogenation and alcohol hydrogenolysis, both of which share the ketyl radical intermediate. This mechanistic understanding enhances our ability to predict and control alcohol hydrogenolysis in the reductive upgrading of biomass-derived oxygenates.